CHEMICAL COMPOSITIONS OF TWO BROWN SEAWEED SPECIES FROM KARIMUN JAWA, INDONESIA - Siahaan, Evi Amelia; Asaduzzaman, A.K.M.; Pangestuti, Ratih (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
Seaweeds are potentials to be developed as alternative source in foods and pharmaceuticals. In this study, chemical compositions of two brown seaweeds species from Karimun Java Indonesia Padina australis and Turbinaria conoides were investigated. Proximate results showed that both seaweeds contain high amount of carbohydrates and ashes. Mineral contents of P. australis and T. conoides follow the orders of Na>Mg>Fe>K>Ca>Zn>Cu and Na>Mg>K>Fe>Zn>Ca>Cu, respectively. Almost all essential amino acids (including histidine, isoleucine, leucine, phenylalanine, threonine, valine and lysine) were present in both seaweeds. Amino acid profiles showed that both seaweed contain polyunsaturated fatty acids (PUFA) with T. conoides contain higher amount of EPA (8.58 Â± 0.22 g/100 g of total fatty acids) and DHA (6.05 Â± 0.21 g/100 g of total fatty acids). The findings of this study have provided evidence that brown seaweeds were nutritious and potential to be utilized for producing functional ingredients in food. Further, P. australis and T. conoides can be used as candidate to be used in food industries to increase shelf-life of food items for human consumption, and use to deter deleterious free radical-induced life-threatening diseases.